Numerical simulation of particle focusing dynamics of DNA-laden fluids in a microtube. (14th December 2019) - Shi, Wei-Dong; Wang, Jian; You, Siming; Yan, Wei-Cheng
Highlights: A transient model considering inertial, elastic and drag force was built. Oldroyd-B fluid model was coupled with a 2D lagrangian model. Particle lateral position monotonically decreases with time. Particles far away from the centerline migrate faster than others. DNA concentration and particle diameter have greater impact on focusing efficiency. Abstract: A CFD model considering inertial, elastic and drag forces was developed to simulate the focusing effect of microparticles in a dilute DNA solution passing through a microtube. The Oldroyd-B fluid model coupled with Lagrangian model was employed to describe the flow behavior of DNA solution and particle trajectory. The model was validated by comparing the patterns of particle beam and its width with experimental results. Particle focusing dynamics was investigated by analyzing the focusing behaviors, flow and particle velocity, and force distributions throughout the whole tube. The results indicated that particles far away from the centerline migrate faster than those near centerline. Investigations on the effect of DNA concentration, particle diameter and flow rate showed that increasing DNA concentration and particle diameter benefited the focusing efficiency while larger flow rate weakened the particle focusing. This computational model could serve as an effective tool to investigate the particle focusing dynamics.